2023
DOI: 10.7759/cureus.33740
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin C in Human Immunity and Its Treatment Potential Against COVID-19: A Review Article

Abstract: The outbreak of the COVID-19 pandemic has left clinicians around the world searching for viable prevention and treatment options to use against the virus. The important physiologic properties of vitamin C have been well documented regarding its use by immune cells and its role as an antioxidant. It has previously shown potential as a prophylactic and treatment option for other respiratory viruses, and because of this, there has been intrigue into whether these positive outcomes translate into a cost-effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In humans, vitamin C supplementation improves the immune system and reduces the severity and duration of infectious diseases ( 71 , 72 ). Studies have shown that vitamin C supplementation may control respiratory tract infections and reduces the mortality of patients with infectious diseases ( 73 ). Vitamin C supplementation (from 50 to 1500 mg/kg/d) can be considered as a complementary treatment for SARS-CoV-2 ( 30 , 74 76 ).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, vitamin C supplementation improves the immune system and reduces the severity and duration of infectious diseases ( 71 , 72 ). Studies have shown that vitamin C supplementation may control respiratory tract infections and reduces the mortality of patients with infectious diseases ( 73 ). Vitamin C supplementation (from 50 to 1500 mg/kg/d) can be considered as a complementary treatment for SARS-CoV-2 ( 30 , 74 76 ).…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with scurvy are highly susceptible to fatal infections, such as pneumonia [ 82 ]. Clinical trials have shown that high doses of Vitamin C have effects against virus infection [ 82 , 83 , 84 , 85 ], and research suggests that the antiviral effect might be attributable to the production of antiviral cytokines (IFNs), free radical formation, or direct binding to the virus [ 86 ]. In addition, vitamin D has shown regulatory effects on both innate immunity and acquired immunity [ 87 ].…”
Section: Natural Products Targeting An Innate Immune Responsementioning
confidence: 99%
“…COVID-19 was declared a pandemic in March 2020 and has infected millions of people worldwide [1,2]. The disease manifested a wide range of clinical symptoms involving several organ systems [3][4][5][6]. The liver is the second most commonly affected organ in COVID-19, following the lungs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%